1994
DOI: 10.1111/j.1460-9568.1994.tb00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Spontaneous GABAA‐mediated Synaptic Events in Rat Hippocampal CA3 Neurons

Abstract: Ongoing spontaneous postsynaptic potentials (SPSPs) were intracellularly recorded at 34-36 degrees C from hippocampal CA3 neurons in slices obtained from postnatal days (P) 0-6 and 7-31. SPSPs occurred randomly, and their frequency distribution was fitted by a single exponential function. They were little affected by kynurenic acid, but were reversibly blocked by bicuculline, implying that they were mediated by GABAA receptors. The mean amplitude was 4.53 +/- 0.89 mV in control conditions and 4.07 +/- 0.79 mV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 37 publications
(51 reference statements)
1
30
0
Order By: Relevance
“…Spontaneous miniature AMPA-mediated EPSCs were recorded in the presence of tetrodotoxin (1 M) from P2-P5 CA1 pyramidal cells at 24°C (n ϭ 7) and 33°C (n ϭ 7). In agreement with previous work (26,27), in some neurons (6͞14) spontaneous glutamatergic activity was not detected (four silent cells were recorded at 24°C and two at 33°C). Bath application of 1 M nicotine, a concentration close to that present in the smoker's blood immediately after smoking a cigarette (28), caused the appearance of mEPSCs ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…Spontaneous miniature AMPA-mediated EPSCs were recorded in the presence of tetrodotoxin (1 M) from P2-P5 CA1 pyramidal cells at 24°C (n ϭ 7) and 33°C (n ϭ 7). In agreement with previous work (26,27), in some neurons (6͞14) spontaneous glutamatergic activity was not detected (four silent cells were recorded at 24°C and two at 33°C). Bath application of 1 M nicotine, a concentration close to that present in the smoker's blood immediately after smoking a cigarette (28), caused the appearance of mEPSCs ( Fig.…”
Section: Resultssupporting
confidence: 93%
“…Quantitative data were derived from eight sections per rat (see Materials and Methods) and two animals per age group. fects, and functional excitatory glutamatergic synaptic transmission is established (Ben-Ari et al, 1989;Hosokawa et al, 1994;Durand et al, 1996;Ben-Ari et al, 1997). This "switch" is accompanied by transient hyperexcitability of the hippocampal network (Gomez-Di Cesare et al, 1997).…”
Section: Potential Developmental Roles Of Gabaergic Crh-ir Neurons Inmentioning
confidence: 99%
“…Previous studies have shown that GABAergic neurons are born prenatally (Schlessinger et al, 1978;Amaral and Kurz, 1985;Lubbers et al, 1985), and by the end of the first postnatal week, they make synaptic contacts on granule cell dendrites as well as somata (Lubbers and Frotscher, 1988;Ribak, 1988, 1990). Although GABAergic responses have been shown to occur in developing hippocampal and cortical pyramidal cells (Mueller et al, 1984;Kriegstein et al, 1987;Janigro and Schwartzkroin, 1988;Ben-Ari et al, 1989;Gaiarsa et al, 1990;Blanton and Kriegstein, 1991;Luhmann and Prince, 1991;Zhang et al, 1991;Hosokawa et al, 1994;Fleidervish and Gutnick, 1995), the functional properties of the early GABA A receptormediated synaptic transmission in the late-developing dentate granule cells are not well understood. The data presented here demonstrate that the overwhelming majority of dentate granule cells of the early postnatal rat possess functionally active GABAergic synaptic inputs [interestingly, no glutamatergic synaptic events can be observed at this time in granule cells (our unpublished observations)], similar to CA1 and CA3 pyramidal cells (Ben-Ari et al, 1989;Hosokawa et al, 1994;Gaiarsa et al, 1995).…”
Section: Early Functional Gabaergic Synapses On Immature Granule Cellsmentioning
confidence: 99%